INSURANCE COMPANY CONTROLLER RESPONSIBILITIES IN CASE OF INSURANCE POLICY FAILURE - Soca Daru Indraswari; Nur Chanifah; Endang Sri Kawuryan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The ambiguity of norms in Article 15 of Insurance Law Number 40 of 2014 has led to multiple interpretations in practice, especially concerning the scope of responsibility for insurance company controllers when there is a policyholder's default, experienced by insurance policyholders at PT Asuransi Jiwasraya in case 676/PDT/2021/PT DKI. This study aims to analyze and determine the scope of responsibility limits for insurance company controllers regarding policyholders' default. This research is a normative study with a legal approach, conceptual and case approaches, and analyzed using grammatical interpretation and systematic interpretation.